(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Abstract - Solar-based E-Uniform furnished with better protection to the soldiers who are working in extreme weather. Solar Panels are wont to power up the interior circuitry of the E-uniform. A 12 V DC lead-acid rechargeable battery is employed for storing the energy. We are using a conventional battery charging unit also for giving supply to the circuitry. ATmega328p microcontroller is the heart of the circuit as it controls all the functions. The project is operated in two modes like summer mode and winter mode. By selecting the mode of operation, we are operating the system such it can drive the body temperature according to heater/cooler. The heater/cooler in turn will help us to provide a chilling or warming effect inside the uniform which helps the soldier to bear to any kind of external environment. The metal sensor will detect the metal-like bomb, any other planted weapon inground and intimate the soldier with a buzzer indication. The wifi is interfaced with the microcontroller and dht11 is additionally interfaced such the tracking of the whole soldier is observed.